2014
DOI: 10.1080/09297049.2014.945407
|View full text |Cite
|
Sign up to set email alerts
|

Local and global aspects of biological motion perception in children born at very low birth weight

Abstract: Biological motion perception can be assessed using a variety of tasks. In the present study, 8- to 11-year-old children born prematurely at very low birth weight (<1500 g) and matched, full-term controls completed tasks that required the extraction of local motion cues, the ability to perceptually group these cues to extract information about body structure, and the ability to carry out higher order processes required for action recognition and person identification. Preterm children exhibited difficulties in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 89 publications
2
15
1
Order By: Relevance
“…Pioneering studies by Braddick and Atkinson () found that, although children born preterm showed both dorsal and ventral stream deficits, global motion perception deficits were more severe as compared to global form discrimination deficits. These findings were confirmed by other studies involving both low‐level and high‐level motion perception processes (Downie, Jakobson, Frisk, & Ushycky, ; MacKay et al., ; Taylor et al., ; Williamson, Jakobson, Saunders, & Troje, ).…”
Section: Discussionsupporting
confidence: 83%
“…Pioneering studies by Braddick and Atkinson () found that, although children born preterm showed both dorsal and ventral stream deficits, global motion perception deficits were more severe as compared to global form discrimination deficits. These findings were confirmed by other studies involving both low‐level and high‐level motion perception processes (Downie, Jakobson, Frisk, & Ushycky, ; MacKay et al., ; Taylor et al., ; Williamson, Jakobson, Saunders, & Troje, ).…”
Section: Discussionsupporting
confidence: 83%
“…Adolescents who were born preterm (GA 27–33 weeks) and previously had PVL were found to have poorer biological motion perception than term‐born controls and children born preterm without PVL . Conversely, a later study reported significantly poorer biological motion perception in children born preterm compared to term‐born controls, but no statistically significant difference in performance between children born preterm with detected abnormalities on neonatal cranial ultrasounds and children born preterm without abnormalities …”
Section: Cortical Processing Of Visual Informationmentioning
confidence: 91%
“…However, other vision problems such as reduced visual fields, impaired contrast sensitivity and cortical processing deficits that have been linked to preterm birth are not routinely screened for, due to time constraints and the need for challenging and/or non‐standardised tests . Such deficits may contribute to the difficulties in learning, attention, behaviour and cognition that some children born preterm experience, despite having normal or near‐normal visual acuity …”
Section: Cortical Processing Of Visual Informationmentioning
confidence: 99%
See 1 more Smart Citation
“…Ten‐year‐old full‐term and preterm adolescents without periventricular leukomalacia (PVL) can be equally sensitive to biological motion, but preterm adolescents with PVL showed reduced sensitivity to biological motion (Pavlova, Sokolov, Birbaumer, & Krägeloh‐Mann, ). Recently, Williamson, Jakobson, Saunders, and Troje () demonstrated that 8‐ to 11‐year‐old premature children with very low birthweight (<1500 g), including those with PVL, performed poorly on biological motion perception as compared with full‐term children. These biological motion perception characteristics in preterm children may be associated with the development of social and communication difficulties (Klin, Lin, Gorrindo, Ramsay, & Jones, ; Pavlova, ).…”
mentioning
confidence: 99%